The effectiveness of chloroquine compared to Fansidar in treating falciparum malaria - Emil Azlin; Ichwan HH Batubara; Wisman Dalimunte; Charles Siregar; Bidasari Lubis; Munar Lubis; Syahril Pasaribu (Paediatrica Indonesiana, 2004)
Background The most difficult problem in eradicating malaria isthe resistance of P. falciparum to drugs. Mandailing Natal has thehighest malaria incidence in North Sumatera.Objective This study aimed to investigate the efficacy of chloro-quine and Fansidar in treating falciparum malaria.Methods A randomized double-blind study was done from April toMay 2001. Eighty-three patients with acute uncomplicated P.falciparum malaria infection were randomized into two groups.Group I (35 patients) received chloroquine and group II (48 pa-tients) received Fansidar. Blood examinations were performed onthe 1 st , 2 nd , 7 th , and 28 th days.Results The resistance of P. falciparum to drugs in the chloro-quine group were found in 10 patients with R II and 1 patients withR III, while in the Fansidar group, there were 14 patients with R II.Conclusion The efficacy of chloroquine and Fansidar in treatingfalciparum malaria was not significantly different